SHARIA BANK ASSET AND LIABILITIES MANAGEMENT STRATEGY: STRATEGI MANAJEMEN ASSET DAN LIABILITAS BANK SYARIAH - Ardha, Vanya; Andini, Liza Ayu; Maharani, Nashwa Balqis (UPMI Proceeding Series, 2023)
High profit income and low risk are the company's targets in maintaining the company, the higher the company's income, the stronger the company is in determining market prices both in the areas of lending and funding, in general and company equity. The purpose of this article is to provide several strategies used by Islamic banking in managing their assets and liabilities in order to avoid the risks that may arise. The method in this article uses library research, which is a method of collecting data by understanding and studying theories from various literature related to this research. The data collection uses ways to find sources and construct from various sources, for example books, journals and research that has been done. The library materials obtained from various references are analyzed critically and must be in-depth in order to support the propositions and ideas. The results of this study provide several strategies used by Islamic banking in managing their assets and liabilities to avoid risks by implementing management functions which include planning, organizing, actuating, and controlling (POAC) in the field of balance sheet structure management, understanding the risks that often happens, applying the three-stage ALMA approach, carrying out the Asset and Liability Management process with planning, fund management, and financing quality management, implementing Asset and Liability Management applications in Islamic banks, and establishing an Asset and Liability Management (ALMA) framework.